Values and influence of religion in public administration - Shanthakumari Sunder, L. (New Delhi ; Thousand Oaks, Calif. : SAGE Publications, 2011)
This book involves a study of the influence of religion, mainly that of Christianity and Hinduism, on the formation of the values in the Indian Civil Service (ICS) and its successor, Indian Administrative Service (IAS). The book deals with the problem of administrative corruption in the IAS, which is the premier civil service of the country. The study attempts to ferret out the root causes of corruption in the Indian society, and especially in the government services like the IAS, through a socio-religious analysis of religion in society. The book is a result of a combination of quantitative and qualitative methods of study that include a thorough survey and in-depth interviews of the serving officers of the Karnataka cadre.
Includes bibliographical references and index.
Keywords: Indian Administrative Service; Civil service -- India; Religion and politics -- India